1984
DOI: 10.1002/clc.4960070804
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory effects of mental stress during exercise in coronary artery disease patients

Abstract: Summary:We examined the effects of mental stress during steady-state exercise on heart rate, blood pressure, pressure-rate product, and oxygen uptake in 10 coronary artery disease patients. Subjects walked at three mph with grade increases of 4% every two minutes until the target heart rate (60 % peak heart rate from a previous symptomlimited exercise test) was reached. A computerized StmpColor-Word Test (mental stress) was added one minute after the subject reached steady-state exercise and lasted 11 5 4 minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Another limitation is that we only studied one type of mental stress and one type of physical stress and the combination of the two. Other types of mental and physical stress may combine differently, as indicated by the literature above (23,36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another limitation is that we only studied one type of mental stress and one type of physical stress and the combination of the two. Other types of mental and physical stress may combine differently, as indicated by the literature above (23,36).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Rousselle et al (27) studied responses to mental arithmetic and seated cycling at 50 W and found that combined physical and mental stresses exert a synergistic impact on cardiac output. Also, Myrtek and Spital (23) and Siconolfi et al (36) reported that the combination of physical and mental stress elicits greater cardiovascular responses than either physical or mental stress alone. Myrtek and Spital (23) employed nonvocal mental arithmetic and supine cycling at 25 W as stresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicate that mental stress alone causes increased heart rate, and the combination of exercise and mental stress produces an additional effect on this same variable. Siconolfi et al 36 found similar results in patients with coronary heart disease. These studies suggest that ventilatory variables are less sensitive than heart rate to the conditions of physical and mental stress.…”
Section: Historical Overview: Estimation Of Energy Expenditure From Pmentioning
confidence: 69%
“…The mental stress test administered was a modification of the Stroop color word test which has been described in detail elsewhere [7]. Briefly, the test consists of a series of confusing words and colors designed to induce mild anxiety and frustration.…”
Section: Mental Stress Testingmentioning
confidence: 99%